Mucuna pruriens, a Possible Treatment for Depressive Disorders - Alfonso Mata-Bermudez; Araceli Diaz-Ruiz; Luis Ricardo Silva-García; Eduardo Manuel Gines-Francisco; Roxana Noriega-Navarro; Camilo Rios; Héctor Alonso Romero-Sánchez; Diego Arroyo; Abraham Landa; Luz Navarro (Neurology International)
Depression is a mental disorder that depicts a wide variety of symptoms, including mood and cognitive alterations, as well as recurrent thoughts of death or suicide. It could become the second leading cause of premature death or disability worldwide. Treatments with conventional antidepressants have several limitations in terms of effectiveness, side effects, and high costs. Therefore, medicinal plants such as Mucuna pruriens are potent candidates for treating depressive disorders. This review shows a compendium of evidence supporting the antidepressant effect of the Mucuna pruriens plant in diverse animal models. This includes the mechanisms of action underlying the antidepressant activity of the treatment concerning dopamine, serotonin, norepinephrine, reactive oxygen species, nitric oxide, cortisol, and inflammation. Clinical trials are needed to study the efficacy and safety of Mucuna pruriens for depression.